Customer perception of mcdonald’s restaurant service quality in kota bharu kelantan - Arulvani A/P Revindaran; Ang Yi Ming; Siti Nuraisyah Abd.Ghafar; Fazzrin Azira Abd Aziz (2023)
The food and beverages sector in Malaysia is now increasingly active, with an increase in the number of local customers. This will also make the food and beverages industry more vibrant, because many local customers make food like McDonalds as their main food such as breakfast, lunch and dinner, especially for customers who work and among students. The purpose of this study is to see the factors that affect customers' perception of McDonald's restaurant service quality in Kota Bharu, Kelantan. These factors are important in making customers satisfied with service quality. The main data of the study will be collected using a structured questionnaire, and the analysis will be done using SPSS software. The survey will be distributed to 348 respondents from McDonald's customers. The food and beverages industry such as McDonald's is growing rapidly, providing a variety of menus with reasonable prices and convenience features when dining in. Through this study, the researcher sought to find out more about the factors that influence customers' perception of McDonald's restaurant service quality in Kota Bharu, Kelantan.